The Added Value of Copper and Silver Metal from Printed Circuit Boards Waste Using Davis Tube with Variations of Size and Magnetic Intensity - Oediyani, Soesaptri; Suwandana, Rahman Faiz; Triana, Tiara; Kusumangingtyas, Dewi; Pradana, Adjie; Syaifara, Zuhrainis (Metalurgi, 2024)
The widespread use of electronic devices has led to a significant increase in electronic waste, including PCB (printed circuit board) waste. PCBs contain valuable metals like copper and silver, which can be reclaimed and reused. Recently, there has been a growing demand for urban mining processes to extract electronic waste PCB Flame Retardant-2 (FR-2) from laptops and computers. During the urban mining process, PCB FR-2 waste undergoes various physical treatments such as dismantling, crushing, and concentration processes. One of the concentration processes involves magnetic separation using a Davis tube. This study aims to investigate the effects of size and magnetic intensity variations on the recovery of copper and silver levels in FR-2 PCB waste. The magnetic concentration process was carried out using different size ranges (-63+100#, -100+150#, -150#) and magnetic intensities (1000 G, 2000 G, 3000 G). The results indicated that the most effective size for separating copper and silver is -63+100# and the optimal magnetic intensity is 1000 G. This resulted in copper and silver content of 45.66% and 0.162%, with recoveries of 80.135% and 62.505% respectively.